Study of the genetic diversity of the aflatoxin biosynthesis cluster in Aspergillus section Flavi using insertion/deletion markers in peanut seeds from Georgia, USA. (4th March 2017) - Faustinelli, Paola C.; Palencia, Edwin R.; Sobolev, Victor S.; Horn, Bruce W.; Sheppard, Hank T.; Lamb, Marshall C.; Wang, Xinye M.; Scheffler, Brian E.; Martinez Castillo, Jaime; Arias, Renée S.
ABSTRACT: Aflatoxins are among the most powerful carcinogens in nature. The major aflatoxin-producing fungi are Aspergillus flavus and A. parasiticus . Numerous crops, including peanut, are susceptible to aflatoxin contamination by these fungi. There has been an increased use of RNA interference (RNAi) technology to control phytopathogenic fungi in recent years. In order to develop molecular tools targeting specific genes of these fungi for the control of aflatoxins, it is necessary to obtain their genome sequences. Although high-throughput sequencing is readily available, it is still impractical to sequence the genome of every isolate. Thus, in this work, the authors proposed a workflow that allowed prescreening of 238 Aspergillus section Flavi isolates from peanut seeds from Georgia, USA. The aflatoxin biosynthesis cluster (ABC) of the isolates was fingerprinted at 25 InDel (insertion/deletion) loci using capillary electrophoresis. All isolates were tested for aflatoxins using ultra-high-performance liquid chromatography. The neighbor-joining, three-dimension (3D) principal coordinate, and Structure analyses revealed that the Aspergillus isolates sampled consisted of three main groups determined by their capability to produce aflatoxins. Group I comprised 10 non-aflatoxigenic A. flavus ; Group II included A. parasiticus ; and Group III included mostly aflatoxigenic A. flavus and the three non-aflatoxigenic A. caelatus . Whole genomes of 10 representative isolates from different groups were sequenced. Although InDels in Aspergillus have been used by other research groups, this is the first time that the cluster analysis resulting from fingerprinting was followed by whole-genome sequencing of representative isolates. In our study, cluster analysis of ABC sequences validated the results obtained with fingerprinting. This shows that InDels used here can predict similarities at the genome level. Our results also revealed a relationship between groups and their capability to produce aflatoxins. The database generated of Aspergillus spp. can be used to select target genes and assess the effectiveness of RNAi technology to reduce aflatoxin contamination in peanut.